IDENTIFIKASI INDIKATOR KEMAMPUAN KOMUNIKASI MATEMATIS PADA SOAL USBN MATEMATIKA SD/MI TAHUN AJARAN 2018/2019 - Erma Wahyu Hutami; Layli Umaya Sari; Ririn Nur Vitasari; Bintang Wicaksono (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
Mathematic communication skills is one of the critical indicator in learning and evaluation of mathematic lesson. But in reality, not all tests accepted by students can upgrade their mathematic communication skills. Meanwhile based on Regulation from National Education Minister Number 22 Year of 2006 it is mentioned that one of the goals of mathematic learning is for students have capability to communicate ideas with symbols, tables, charts, and any other media to clarify the conditions or problems. Based on that it is necessary to identify mathematic communication skills indicator on mathematic tests. Moreover on the mathematic USBN, where the results determine the students’s final score. The mathematic communication skills indicator which would be identified were: 1) connects the real things, picture and charts to the mathematic ideas, 2) explains ideas, situations and mathematic relations with speech or texts with real things, pictures, graphs and algebra, 3) listens, discusses and writes about mathematics, 4) states daily activity in mathematic languace, 5) reads with understanding about written mathematic presentation, 6) makes mathematic statement which is relevant with problem situation, and 7) makes conjectures, arguments, determines definition and generalisation. In here the mathematic communication skills that would be analyzed was students capability to solve contextual problems. On Mathematic .USBN for Elementary School in the year 2018/2019 there were 35 problems, where 30 problems were multiple choice and 5 were essay. There were few problems contains mathematic communication skills indicator which were number 31, 32, 33, 34, 35